Empirical study on the three anormalies of the U.S. IPO market - Ang, Sze Ming (2008)
The group investigates the initial returns and long run stock performance of U.S. firms after their initial public offering (IPO). A total of 5,262 firms listed on the U.S. stock markets from 1982 to 2001 are included in our sample.